Enhancing Religious Education through the Integration of School-Based Worship Activities: A Strategic Approach - Nurhasanah Sipahutar; Mardianto Mardianto (Institut Agama Islam An-Nawawi Purworejo, 2024)
This research explores the integration of religious activities in State Elementary School (SDN) No 116260 Simonis North Sumatra to strengthen religious education among students, with a special focus on Friday worship activities. This research aims to identify the forms of Friday worship activities, their implementation, as well as the supporting and inhibiting factors that influence these activities in strengthening students' religious education. The research method used is qualitative using data collection techniques in the form of observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. The results show that Friday worship activities have a significant impact on students, increasing their understanding of worship and enabling them to carry out compulsory worship such as prayer and reading the Qur'an. Friday worship activities generally include dhuha prayers in congregation, reading the Qur'an, sholawat and dhikr, and kultum. Supporting factors include adequate facilities at the school, support from the principal, cooperation between teachers and parents, and students' enthusiasm in participating in these activities. However, the main inhibiting factor identified was the limited implementation time. In conclusion, the integration of religious activities such as Friday worship contributes positively to strengthening students' religious education, improving understanding and practice of religious obligations in educational institutions.